Methods in empirical prosody research - Sudhoff, Stefan; Pappert, Sandra (Language, context, and cognition, 2006)
Acoustic segment durations in prosodic research / Alice Turk, Satsuki Nakai & Mariko Sugahara -- Stylization of pitch contours / Dik J. Hermes -- Voice source parameters and prosodic analysis / Christophe d'Alessandro -- Prosody beyond fundamental frequency / Greg Kochanski -- Paradigms in experimental prosodic analysis / Klaus J. Kohler -- Information structure and prosody / Stefan Baumann -- Time types and time trees / Dafydd Gibbon -- Probing the dynamics of speech production / Fred Cummins -- Using interactive tasks to elicit natural dialogue / Kiwako Ito & Shari R. Speer -- Online methods for the investigation of prosody / Duane G. Watson, Christine A. Gunlogson & Michael K. Tanenhaus -- How to obtain and process perceptual judgements of intonational meaning / Toni Rietveld & Aoju Chen -- Experimental approaches to establishing discreteness of intonational contrasts / Carlos Gussenhoven -- Phonetic grounding of prosodic categories / Katrin Schneider ... [et al.]